2020
DOI: 10.1007/s00453-020-00706-6
|View full text |Cite
|
Sign up to set email alerts
|

On Cycle Transversals and Their Connected Variants in the Absence of a Small Linear Forest

Abstract: A graph is H-free if it contains no induced subgraph isomorphic to H. We prove new complexity results for the two classical cycle transversal problems Feedback Vertex Set and Odd Cycle Transversal by showing that they can be solved in polynomial time on (sP1 + P3)-free graphs for every integer s ≥ 1. We show the same result for the variants Connected Feedback Vertex Set and Connected Odd Cycle Transversal. We also prove that the latter two problems are polynomial-time solvable on cographs; this was already kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 40 publications
2
27
0
Order By: Relevance
“…Both problems are polynomial-time solvable for P 4 -free graphs [5], for sP 2 -free graphs for every s ≥ 1 [8] and for (sP 1 + P 3 )-free graphs for every s ≥ 1 [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both problems are polynomial-time solvable for P 4 -free graphs [5], for sP 2 -free graphs for every s ≥ 1 [8] and for (sP 1 + P 3 )-free graphs for every s ≥ 1 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Odd Cycle Transversal is NP-complete for (P 2 + P 5 , P 6 )-free graphs [13]. Very recently, Abrishami et al showed that Feedback Vertex Set is polynomial-time solvable for P 5 -free graphs [1].…”
Section: Introductionmentioning
confidence: 99%
“…This in particular applies to the Odd Cycle Transversal problem. We note here that Dabrowski et al [16] proved that Odd Cycle Transversal in {P 6 , K 4 }-free graphs is NP-hard and does not admit a subexponential-time algorithm under the Exponential Time Hypothesis. Thus, it is unlikely that any of our algorithmic results -the n O(ω(G)) -time algorithm and the n O( √ n) -time algorithm -can be extended from P 5 -free graphs to P 6 -free graphs.…”
Section: Finding Large H-colorable Subgraphs In Hereditary Graph Classesmentioning
confidence: 85%
“…For k = 2 it can be expressed as Maximum Induced Bipartite Subgraph, which by complementation is equivalent to the well-studied Odd Cycle Transversal problem: find the smallest subset of vertices that intersects all odd cycles in a given graph. While polynomial-time solvability of Odd Cycle Transversal on P 4 -free graphs (also known as cographs) follows from the fact that these graphs have bounded cliquewidth (see [15]), it is known that the problem is NP-hard in P 6 -free graphs [16]. The complexity status of Odd Cycle Transversal in P 5 -free graphs remains open [9,Problem 4.4]: resolving this question was the original motivation of our work.…”
Section: :3mentioning
confidence: 99%
“…Hence, both problems are NP-complete for H-free graphs if H has a cycle or claw. Both problems are polynomial-time solvable for P 4 -free graphs [5], for sP 2 -free graphs for every s ≥ 1 [8] and for (sP 1 + P 3 )-free graphs for every s ≥ 1 [13].…”
Section: Introductionmentioning
confidence: 99%